Isolation and characterization of Dehalobacter sp. strain UNSWDHB capable of chloroform and chlorinated ethane respiration. (30th April 2016) - Wong, Yie K.; Holland, Sophie I.; Ertan, Haluk; Manefield, Mike; Lee, Matthew
Summary: Dehalobacter sp. strain UNSWDHB can dechlorinate up to 4 mM trichloromethane at a rate of 0.1 mM per day to dichloromethane and 1, 1, 2‐trichloroethane (1 mM, 0.1 mM per day) with the unprecedented product profile of 1, 2‐dichloroethane and vinyl chloride. 1, 1, 1‐trichloroethane and 1, 1‐dichloroethane were slowly utilized by strain UNSWDHB and were not completely removed, with minimum threshold concentrations of 0.12 mM and 0.07 mM respectively under growth conditions. Enzyme kinetic experiments confirmed strong substrate affinity for trichloromethane and 1, 1, 2‐trichloroethane ( K m = 30 and 62 µM respectively) and poor substrate affinity for 1, 1, 1‐trichloroethane and 1, 1‐dichloroethane ( K m = 238 and 837 µM respectively). Comparison of enzyme kinetic and growth data with other trichloromethane respiring organisms ( Dehalobacter sp. strain CF and Desulfitobacterium sp. strain PR) suggests an adaptation of strain UNSWDHB to trichloromethane. The trichloromethane RDase (TmrA) expressed by strain UNSWDHB was identified by BN‐PAGE and functionally characterized. Amino acid comparison of homologous RDases from all three organisms revealed only six significant amino acid substitutions/deletions, which are likely to be crucial for substrate specificity. Furthermore, strain UNSWDHB was shown to grow without exogenous supply of cobalamin confirming genomic‐based predictions of a fully functional cobalamin synthetic pathway.